JSE market reaction to employee satisfaction survey: does the stock market fully value intangibles? - Alcock, Richard Albert (My University, 2015)
For some people, it may seem obvious that companies perform better if their employees are happier, but this relationship is not as obvious as it might seem. Extensive research indicates that intangible-intensive assets such as a skilled workforce, patents and know-how, software, strong customer relationships, unique organisational design and processes, brand and employee satisfaction are often mispriced by markets. Investors, more often than not, undervalue intangibles. This research report examines whether a positive relationship exists between employee satisfaction and firm value and whether this relationship is taken into account by the stock market. Using event study methodology, the study shows that within the South African context, a cross section of JSE listed companies, little evidence exists that would suggest a positive correlation between employee satisfaction and firm value. Where such a relationship does exist it is mispriced by the market. The report concludes that, considering the high value placed on people as one of the most important assets of firms today, and based on the vast body of evidence presented by previous studies in favour of a positive correlation between intangible assets such as employee satisfaction and firm value, that one cannot dispel the fact that these findings have implications for human resource management workplace practises.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.